Optimizing treatment persistence in epilepsy: a comparative analysis of combined antiseizure medications with different mechanisms of action - Chun-Wei Chang; Wei-En Johnny Tseng; Wey-Ran Lin; Po-Chuan Ko; Chun-Jing Liu; Siew-Na Lim (Therapeutic Advances in Neurological Disorders, 2023)
Background: Combination therapy with antiseizure medications (ASMs) is a rational strategy if monotherapy cannot effectively control seizures, thereby aiming to improve tolerance and treatment persistence. Objectives: To compare the efficacy of different ASM combinations among patients. Design: Patients with epilepsy on monotherapy who had a second ASM added as concomitant two-drug therapy from January 2009 to May 2019 in the Chang Gung Research Database, Taiwan, were included in the analysis. Methods: ASM combinations were compared based on their primary mechanism of action (MoA) which are as follows: gamma-aminobutyric acid receptor (G), sodium channel blocker (SC), synaptic vesicle protein 2A (SV2), calcium channel blocker (C), and multiple mechanisms (M). Treatment persistence was compared, and the predictors of persistence were analyzed. Results: In total, 3033 patients were enrolled in this study. Combined ASMs with different MoAs had significantly longer treatment persistence than ASMs with similar MoAs, specifically SC and M combinations. Patients receiving combined ASMs with different MoAs were less likely to discontinue treatment [adjusted hazards ratio: 0.83 (95% CI: 0.75–0.93), p  < 0.001]. Among all combinations, the SC + SV2 combination had the longest treatment persistence (mean ± SD: 912.7 ± 841.6 days). Meanwhile, patients receiving the G combination had a higher risk of treatment discontinuation than those receiving the SC + SV2 combination. Underlying malignancies were associated with an increased risk of treatment discontinuation across all MoA categories. Male patients receiving the SC, SV2, and M combinations were more likely to discontinue treatment than female patients. Moreover, patients with renal disease were more likely to discontinue treatment with the SV2 combinations. Conclusion: ASM combinations with different MoAs had superior efficacy and tolerability to ASM combinations with similar MoAs, particularly SC and M combinations. In our cohort, factors associated with treatment discontinuation included underlying malignancy, male sex, and renal disease. These findings may provide valuable insights into the use of ASM combinations if monotherapy cannot adequately control seizures.